(b) Solve the following quadratic equations by using the quadratic formula, giving the solu simplified Surd form. \( \begin{array}{ll}\text { (i) } 5 x^{2}+2 x+1=0 & \text { (ii) } 7 x^{2}+9 x+1=0\end{array} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To solve these quadratic equations using the quadratic formula, we use the formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \). (i) For the equation \( 5x^2 + 2x + 1 = 0 \), we have \( a = 5 \), \( b = 2 \), and \( c = 1 \). The discriminant \( b^2 - 4ac = 2^2 - 4(5)(1) = 4 - 20 = -16 \). Since the discriminant is negative, the solutions will be complex: \[ x = \frac{-2 \pm \sqrt{-16}}{10} = \frac{-2 \pm 4i}{10} = \frac{-1 \pm 2i}{5}. \] (ii) For the equation \( 7x^2 + 9x + 1 = 0 \), we have \( a = 7 \), \( b = 9 \), and \( c = 1 \). The discriminant \( b^2 - 4ac = 9^2 - 4(7)(1) = 81 - 28 = 53 \). Since it's positive, the solutions are real: \[ x = \frac{-9 \pm \sqrt{53}}{14}. \] Therefore, the simplified surd forms of the solutions are: (i) \( x = \frac{-1 \pm 2i}{5} \) and (ii) \( x = \frac{-9 \pm \sqrt{53}}{14} \).